2020
DOI: 10.1038/s41598-020-61877-4
|View full text |Cite
|
Sign up to set email alerts
|

A photoperiodic time measurement served by the biphasic expression of Cryptochrome1ab in the zebrafish eye

Abstract: The zebrafish (Danio rerio) is a model species that is used to study the circadian clock. it possesses light-entrainable circadian clocks in both central and peripheral tissues, and its core circadian factor cryptochromes (CRYs) have diverged significantly during evolution. In order to elucidate the functional diversity and involvement of cRYs in photoperiodic mechanisms, we investigated the daily expression profiles of six Cry transcripts in central (brain and eye) and peripheral (fin, skin and muscle) tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…zCry1ab , as previously reported [ 22 ], showed two peaks near the beginning of the light period (ZT23.7 in LD; ZT21.5 in SD) and just before the end (ZT13.0 in LD; ZT9.0 in SD), under both LD and SD conditions (Fig. 2 c and d; Table 1 ).…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…zCry1ab , as previously reported [ 22 ], showed two peaks near the beginning of the light period (ZT23.7 in LD; ZT21.5 in SD) and just before the end (ZT13.0 in LD; ZT9.0 in SD), under both LD and SD conditions (Fig. 2 c and d; Table 1 ).…”
Section: Resultssupporting
confidence: 86%
“…We previously compared the expression profiles of the Cry genes in the zebrafish eye and reported that their peak times could be located on midnight-morning and evening periods, and that Cry1ab has a double peak [ 22 ]. In this study, expression profiles of 16 Cry genes were obtained by evaluating the gene expression every 2 h, under different photoperiods (14L10D and 10L14D) and in the constant dark just after the different photoperiodic entrainments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations